Pengaruh Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan pada Perusahaan Start-Up - Bachri, Syaiful; Mandasari, Puti (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
Transformational leadership is believed to be an approach capable of improving employee performance, particularly in start-up companies characterized by fast-paced work dynamics, high innovation, and intense competition. This study aims to determine the effect of transformational leadership on employee performance in start-up companies. The research method used a quantitative approach with a survey design, involving 80 employee respondents from several start-up companies. The research instrument was a Likert-scale questionnaire analyzed using simple linear regression. The results showed that transformational leadership has a positive and significant effect on employee performance, contributing 62%. This proves that the higher the implementation of transformational leadership, the better employee performance.